A HISTORICAL OVERVIEW OF WAQF - Abid, Obaidullah; Miakhil, Sarferaz (International Journal of Sukuk and Waqf Research, 2024)
This research delves into the historical evolution of Waqf, an Islamic philanthropic institution with centuries-old roots. Tracing its origins to early Islamic societies, the study examines how Waqf has adapted to diverse cultural landscapes and contributed to social welfare. Through an interdisciplinary approach, it explores legal frameworks, socio-economic impacts, and the role of Waqf in shaping communities. This historical overview aims to deepen understanding of Waqf's enduring significance and implications for contemporary socio-economic structures. The main objective of this research is to undertake an overall relevance of the historical Waqf in the Islamic Economic system. It will elaborate on Waqf juristically, classically and modernly. The study explored various aspects such as Waqf's meaning, different definitions by several religious schools of thought, historical origins, and legitimacy of the Waqf based on Quranic Verses and Hadith of the Prophet (PBUH). Throughout Islamic civilization, Waqf played a vital role in Muslim society, given that the needs of the Muslim Ummah were complex and growing. The objective of Waqf is to promote social welfare and to contribute to economic development. The potential of the institution of Waqf is excellent; it can assist the government in countless state responsibilities.JEL Classification Codes: N35.